Public policy and institutional challenges in the achievement of sustainable agriculture - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
First, the document notes that sustainable development is attracting the attention of the international community within the framework of what is refered to as the World's Common Future (Brundtland Commision 1987). To achieve common interest it is necessary to analyze economic relations among countries, particularly between North and South, as well as within nations, and between rural and urban societies. The document recommends that commitment must be global, multiparty and multisectoral. Within the realm of agriculture, achieving sustainability requires a multidisciplinary effort, and clear interinstitutional relations. For that reason, this work attempts to produce a policy framework that does not only consider onfarm and agroindustrial technology, but also communal rural society and domestic and international trade, with particular focus on the latter. Section 2 focuses on the policy issues that arise in the pursuing of sustainable agriculture and the need for institutional capabilities in specific areas where policies are required. Section 3 highlights the government responsibilities and needs for adequate institutions able to guide the sustainable development of agriculture. In this section, particular reference is made to the need for appropriate information to develop policies and for an appraisal fo the extent to which sustainability has been achieved so far.